Geochemical distribution and fate of arsenic in water and sediments of rivers from the Hokusetsu area, Japan - Emilie Even; Harue Masuda; Takahiro Shibata; Aki Nojima; Yusuke Sakamoto; Yusuke Murasaki; Hitoshi Chiba (Journal of Hydrology: Regional Studies, 2017)
Study region: Hokusetsu Region in Osaka, Japan. Study focus: The As contamination was investigated through the geochemical mapping and analysis of river waters and bed sediments over an area of 440 km2. Sulfur from sulfides in rocks and dissolved sulfates in water were compared via isotopic analysis to assess their origin and the subsequently released As. The fate of As (transport, binding on settling particles) was evaluated through the total and dissolved fractions of As and trace metals Fe, Mn and Al in river waters. New hydrological insights for the region: The geochemical mapping showed that As in river water exceeded the maximum limit concentration of 10 ppb in several places. The highest As levels (waters and sediments) correlated well with the surface geologies, concentrating in a halo around granitic intrusion and nearby faults. The isotopic analysis of sulfur revealed the occurrence of two kinds of sulfide mineralizations responsible for As contamination: one from Late Paleozoic submarine volcanism in sedimentary rocks, and one from Late Cretaceous igneous activities in contact-metamorphosed rocks disseminated with sulfides. The transport of As along river courses occurred mainly as a dissolved species rather than absorbed on Fe/Mn/Al particles, signifying the least role of iron oxy-hydroxides in As adsorption.